Dengue virus type 2 (DENV2)-induced oxidative responses in monocytes from glucose-6-phosphate dehydrogenase (G6PD)-deficient and G6PD normal subjects. - Abdullah Ahmed Al-Alimi (PLoS Neglected Tropical Diseases, 2014)
BACKGROUND: Dengue virus is endemic in peninsular Malaysia. The clinical manifestations vary depending on the incubation period of the virus as well as the immunity of the patients. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is prevalent in Malaysia where the incidence is 3.2%. It has been noted that some G6PD-deficient individuals suffer from more severe clinical presentation of dengue infection. In this study, we aim to investigate the oxidative responses of DENV2-infected monocytes from G6PD-deficient individuals. METHODOLOGY: Monocytes from G6PD-deficient individuals were infected with DENV2 and infection rate, levels of oxidative species, nitric oxide (NO), superoxide anions (O2-), and oxidative stress were determined and compared with normal controls. PRINCIPAL FINDINGS: Monocytes from G6PD-deficient individuals exhibited significantly higher infection rates compared to normal controls. In an effort to explain the reason for this enhanced susceptibility, we investigated the production of NO and O2- in the monocytes of individuals with G6PD deficiency compared with normal controls. We found that levels of NO and O2- were significantly lower in the DENV-infected monocytes from G6PD-deficient individuals compared with normal controls. Furthermore, the overall oxidative stress in DENV-infected monocytes from G6PD-deficient individuals was significantly higher when compared to normal controls. Correlation studies between DENV-infected cells and oxidative state of monocytes further confirmed these findings. CONCLUSIONS/SIGNIFICANCE: Altered redox state of DENV-infected monocytes from G6PD-deficient individuals appears to augment viral replication in these cells. DENV-infected G6PD-deficient individuals may contain higher viral titers, which may be significant in enhanced virus transmission. Furthermore, granulocyte dysfunction and higher viral loads in G6PD-deificient individuals may result in severe form of dengue infection.